Pola Okupasi Ruang Publik oleh Organisasi Kepemudaan di Kota Medan Sumatera Utara - Budi Syaputra; Hidayat Amsani; Ichwan Azhari (Universitas Negeri Medan, 2020)
This paper aims to determine the patterns of occupation of public space and land tenure carried out by the Youth Organization in the City of Medan. The intended public space is a parking lot, security of traditional markets and entertainment venues, located in a location controlled by one of the youth organizations, this location must be protected so that it is not controlled by other youth organizations. The research method used is the qualitative method with ethnographic approach and data collection techniques using participant observation and interviews. The results of this study explain the pattern carried out in controlling this public space by collaborating (patron-client) with related parties such as regional market companies, the Department of Transportation and the City Government. The collaboration was carried out by providing a number of accommodation funds to the service in the form of deposits and tenders. The cooperating with private parties such as property developers in order to get permission to provide building materials, the tender for the supply of project materials must pass the youth organization, In launching occupation of public space and land tenure. Not a few of the leaders or members of the Youth Organization entered the political sphere such as becoming a member of the DPRD, so the member had the power to distribute tenders or government projects or private.